1995
DOI: 10.1093/ajcp/104.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation Markers in Breast Carcinoma:Mitotic Figure Count, S-Phase Fraction, Proliferating Cell Nuclear Antigen, Ki-67 and MIB-1

Abstract: Proliferative rate is an important prognostic marker in breast carcinoma. However, the best measurement method has not been established. This study evaluated mitotic figure counts (MFC) as mitoses per 10 high power fields (HPF) and per 1,000 cells, S-phase fraction by flow cytometry, and Ki-67, MIB-1, and proliferating cell nuclear antigen (PCNA) positivity by immunohistochemistry in 135 breast carcinomas. There was strong correlation between the two MFC methods and significant correlation between MIB-1 positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
76
4
7

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(101 citation statements)
references
References 0 publications
14
76
4
7
Order By: Relevance
“…59 -62 Our results were at odds with reports in the literature, including 12 of 12 studies that showed positive correlations were between Ki-67 and mitotic activity 45,47,54,[62][63][64][65][66][67][68][69][70] and 8 of 9 studies that showed a correlation between Ki-67 and SPF. 49,53,[65][66][67][71][72][73] The same results that we produced were reported in the literature concerning Scarff-Bloom grade in 23 of 23 reports, 45-51,53-56,58,65,69 -71,73-79 concerning p53 in 12 of 14 reports, 48,54,58,65,72,75,77,80 -84 and concerning hormone receptor status in 19 of 24 reports. 46 -48,52,54,55,58,62,63,69,70,72,73,76,77,83-86 p21 was not correlated with any clinicopathologic factor or biologic marker.…”
Section: Discussionsupporting
confidence: 81%
“…59 -62 Our results were at odds with reports in the literature, including 12 of 12 studies that showed positive correlations were between Ki-67 and mitotic activity 45,47,54,[62][63][64][65][66][67][68][69][70] and 8 of 9 studies that showed a correlation between Ki-67 and SPF. 49,53,[65][66][67][71][72][73] The same results that we produced were reported in the literature concerning Scarff-Bloom grade in 23 of 23 reports, 45-51,53-56,58,65,69 -71,73-79 concerning p53 in 12 of 14 reports, 48,54,58,65,72,75,77,80 -84 and concerning hormone receptor status in 19 of 24 reports. 46 -48,52,54,55,58,62,63,69,70,72,73,76,77,83-86 p21 was not correlated with any clinicopathologic factor or biologic marker.…”
Section: Discussionsupporting
confidence: 81%
“…Different antibodies were used through all trials: anti-Ki-67 was used in 24 studies (52.1%), anti-MIB-1 in 24 studies (52.1%), both antibodies were performed in five studies (Keshgegian and Cnaan, 1995;Veronese et al, 1995;Bevilacqua et al, 1996;Querzoli et al, 1996;Billgren et al, 2002), anti-Ki-S5 in two studies (Rudolph et al, 1999a;Esteva et al, 2004) and anti-Ki-S11 in one study (Rudolph et al, 1999b). The different cut-off values used were those of the authors (range: 3.5 -34%).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…The murine monoclonal antibody Ki-67 reacts with a human nuclear antigen that is expressed in G1, S, G2, and mitosis, but not in G0 (Gerdes et al, 1984). In breast cancer, a strong correlation has been found between the percentage of cells positive for Ki-67 and nuclear grade and mitotic rate (Sahin et al, 1991;Keshgegian 1995).…”
Section: Introductionmentioning
confidence: 99%